Pelatihan Komunikasi Pemasaran Digital dalam Mempromosikan Gerabah Desa Banyumulek, Kediri, Kabupaten Lombok Barat - Muhlis Muhlis; Hartin Nur Khusnia; Yulanda Trisula Sidarta Yohanes (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
Banyumulek Village, Kediri, West Lombok, is a famous pottery producer and visited by many tourists. However, the COVID-19 pandemic resulted in fewer tourists visiting Lombok, thus affecting the sales of pottery produced by Banyumulek Village. Based on this background, this service activity aims to support the promotion of pottery produced by Banyumulek Village residents through digital marketing communication training. The method of implementing this activity is to socialize the importance of using digital media as an online marketing tool during the pandemic and teach participants how to create creative content and attract public attention by utilizing social media to promote Banyumulek Village pottery products. From the results of the activity, it is known that the majority of participants (88.23%) have used social media as promotional media, of which 38.89% used Facebook, 33.33% used WhatsApp, and 27.78% used Facebook, Instagram, and WhatsApp as social media in promoting pottery products. However, the less attractive message design makes the results will be not optimal. To that end, the service team shared knowledge and hands-on practice regarding the preparation of instant messages and shooting techniques to obtain materials or digital promotional content for Bayumulek Village pottery products on the participants' social media.